Factors that influence the decision to use videoconferencing apps: drivers and inhibitors - Oliveira, António Maria Dourdil Bispo Pessanha de (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence